Photosynthetic Response of Soybean Leaf to Wide Light-Fluctuation in Maize-Soybean Intercropping System - Yao, Xingdong; Zhou, Hongli; Zhu, Qian; Li, Chunhong; Zhang, Huijun; Wu, Jun-Jiang; Xie, Futi (Frontiers in Plant Science, 2017)
In maize-soybean intercropping system, soybean plants will be affected by the wide light-fluctuation, which resulted from the shading by maize plants, as the shading of maize the light is not enough for soybean in the early morning and late afternoon, but at noon, the light is strong as the maize shading disappeared. The objective of this study is to evaluate the photosynthetic response of soybean leaf to the wide light-fluctuation. The data of diurnal variation of photosynthetic characters showed that the photosynthetic rate of intercropped soybean was weaker than that of monocropped soybean. The chlorophyll content, ratio of chlorophyll a/b, and AQE (apparent quantum efficiency) were increased and Rd (dark respiration rate) was decreased for the more efficient interception and absorption of light and carbon gain in intercropping. δRo (The efficiency/probability with which an electron from the intersystem electron carriers was transferred to reduce end electron acceptors at the PSI acceptor side) and φRo (the quantum yield for the reduction of the end electron acceptors at the PSI acceptor side) in intercropped were lower compared to those in monocropped one, which showed that the acceptor side of PSI might be inhibited, and also it was the main reason that intercropped soybean showed a low photosynthetic capacity. ψEo (The efficiency/probability with an electron moves further than QA-) in monocropping and intercropping decreased 5.8% and 35.7%, respectively, while φEo (quantum yield for electron transport) decreased 27.7% and 45.3% under the high radiation at noon, which suggested that the acceptor side of PSII was inhibited, while the NPQ became higher. These were beneficial to dissipate excess excitation energy in time, and protect the photosynthetic apparatus against photo-damage. The higher performance index on the absorption basis (PIABS) and lower δRo, φRo, ψEo and φEo of intercropped soybeans compared to monocropping under high radiation indicated that the electron transfer of intercropped soybean was inhibited more seriously and intercropped soybean adjusted the electron transport between PSII to PSI to adapt the light-fluctuation. Higher NPQ capacity of intercropped soybeans played a key role in keeping the leaf with a better physiological flexibility under the high radiation.